Analisis Pengendalian Kualitas Produksi Papan Fiber Semen dengan Metode Seven Tools dan FMEA pada PT. XYZ - Vidiah Nur’Aini; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2024)
Product failure is a problem that always exists in the manufacturing industry. This analysis is carried out to determine the types of defects that often arise and the factors that cause product failure that arise that affect product quality at PT. XYZ. This analysis checks the quality control steps carried out in the fiber cement board production process. Aims to determine the cause and effect of production defects at PT. XYZ by using seventools and fmea (Failure Mode and Effect) methods. taken from production data at PT. XYZ in December 2022 – May 2023, with a total production of 1,173,690 pcs and a total number of defects of 72. 848 pcs for six months. The results of the analysis that can be known are the number of types of cracked product defects is the most dominant cacan with a total of 16,307 pcs, the cause of product defects can be caused by machine factors and seen from the results of avoidance the RPN risk priority number is 392.